(untitled) (Ho Chi Minh City, 2012)
Synthesis and characterisation of metal-free thiocarbamoyl chitosan gel, antioxidant and antibacterial chitosan film based on polydopamine modification,...
Keywords: Chitin,Chitosan,Chitin,Chitosan; Biotechnology,Biotechnology,Công nghệ sinh học,Công nghệ sinh học